Towards a Circular Economy: Government Policy in Waste Management Based on the 3R Concept in Makassar City, Indonesia - Akramila, Nurul; A. Mappasere, Fatmawati; Mahsyar, Abdul (Universitas Muhammadiyah Yogyakarta, 2025)
Ineffective waste management can lead to the accumulation of waste, which results in environmental damage and low economic income for the community. The purpose of this study was to analyse the participation of the community in the implementation of the 3R circular economy in Makassar City. Qualitative research methods were used in this study. The data sources of this research were collected through interviews, observations, and study of relevant documents. Secondary data was collected by searching data from the Google Scholar database using the Publish or Perish application and Vos Viewer to map the topic. The results and discussion also used the NVivo 12 Plus